Impact of formulation and particle size on stability and immunogenicity of oil-in-water emulsion adjuvants - Iyer, Vidyashankara (Hum Vaccin Immunother, 2015)
Oil-in-water emulsions have gained consideration as vaccine adjuvants in recent years due to their ability to elicit a differentiated immunogenic response compared to traditional aluminum salt adjuvants. Squalene, a cholesterol precursor, is a natural product with immunostimulatory properties, making it an ideal candidate for such oil-in-water emulsions. Particle size is a key parameter of these emulsions and its relationship to stability and adjuvanticity has not been extensively studied. This study evaluates the effect of particle size on the stability and immunogenicity of squalene emulsions. We investigated the effect of formulation parameters such as surfactant concentration on particle size, resulting in particles with average diameter of 80 nm, 100 nm, 150 nm, 200 nm, or 250 nm. Emulsions were exposed to shear and temperature stresses, and stability parameters such as pH, osmolarity, size, and in-depth visual appearance were monitored over time. In addition, adjuvanticity of different particle size was assessed in a mouse model using Respiratory Syncytial Virus Fusion protein (RSV-F) as a model antigen. Temperature dependent phase separation appeared to be the most common route of degradation occurring in the higher particle sizes emulsions. The emulsions below 150 nm size maintained stability at either 5°C or 25°C, and the 80 nm diameter ones showed no measurable changes in size even after one month at 40°C. In vivo studies using the emulsions as an adjuvant with RSV F antigen revealed that superior immunogenicity could be achieved with the 80 nm particle size emulsion.